광주 지역 건강검진센터를 내원한 수진자의 인스턴트 커피믹스 섭취와 대사적 위험요인과의 연관성 - 김경윤(Kyoung Yun Kim); 양수진(Soo Jin Yang); 윤정미(Jung-Mi Yun) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
Metabolic syndrome is associated with risk of developing cardiovascular disease and type 2 diabetes, and incidence of metabolic syndrome is showing an increasing trend. Recently, coffee intake is argued to have an effect on the gut-brain axis, and it is widely recognized has being associated with many beneficial effects, including those related to metabolic imbalance. However, it is essential to understand how the dietary aspects of coffee intake and type of coffee intake affect diet and overall health. The association between coffee consumption and health is still controversial, and the average body weight of the Korean population is increasing. Therefore, this study focused on analyzing the effects of instant coffee (particularly instant coffee mix) in Korea, especially with respect to metabolic syndrome. The study was conducted on participating subject's that visited Sun-Han hospital, and instant coffee mix intakes and metabolic risk factors during the study period were examined from July 2015 to June 2016. The results showed that waist circumference (r=0.405, P=0.036) and serum triglyceride level (r=0.435, P=0.023) were positively correlated with instant coffee mix intakes. In addition, instant coffee mix intakes were significantly associated with serum triglyceride level in subjects who consumed more than 1 cup/d of coffee (P<0.05). Therefore, subjects should be careful about fat intake and be educated about the type and frequency of coffee intakes. 본 연구는 2015년 7월부터 2016년 6월까지의 연구기간 동안 내원한 광주선한병원의 건강검진 수진자들의 인스턴트 커피믹스 섭취량을 조사하여 대사증후군 위험인자와의 연관성을 분석하고자 하였다. 그 결과 인스턴트 커피믹스 섭취와 대사증후군의 위험인자 중 특히 허리둘레와 혈중 중성지방 농도는 양의 상관성을 보였고, 인스턴트 커피믹스 섭취빈도가 증가할수록 공복혈당과 혈중 중성지방 농도가 증가하는 유의적인 상관성을 보였다. 또한, 다중회귀분석에서도 1 cup/d 이상 인스턴트 커피믹스를 섭취하는 대상자에서 보정 여부와 상관없이 대사증후군 위험인자인 혈중 중성지방 농도가 상승하는 유의적인 연관성을 나타냈다. 이와 같은 인스턴트 커피믹스와 관련한 연구 조사와 선행 연구 결과를 통하여 볼 때 건강인은 물론 지방 섭취에 주의해야 할 대상자는 섭취 커피 종류에 따른 섭취 빈도와 섭취량 조절 교육이 중요하다.